The Trend of Residential-Livelihood Changes in Nomadic Ecosystems with Environmental Sustainability Approach (Case Study: Farsimadan Tribe Ecosystem, Fars Province) - Siamak Tahmasbi; Seyed Ali Badri; Mohammad Reza Rezvani (جغرافیا و پایداری محیط, 2016)
1- Introduction Throughout the history, human has always experienced three diverse social systems with economic, cultural and political conditions. Since the beginning of the industrial revolution, the technology gradually has been influencing all aspects of human life. Therefore, with the development of technology, shift of production centers and lifestyle and urbanization gradually dominated rural and nomadism settlement in developed countries. Affected by the current socio-economic and political changes at national level, tribal communities have undergone a dramatic transformations in various aspects such as migration and settlement status, type of housing, having service and facilities, the exploitation status of livestock, farming and gardening, livestock feeding sources, socioeconomic structure and traditional patterns of mobility of them. Qashqai tribe, as one of the nomadic tribes, has experienced vast changes in residential- Livelihood affected by involuntary hesitancy policies and perspective modernization of Reza khan era resulting in hesitancy and migration to urban centers. This research aimed at studying Farsimadn sub tribe to seek understanding transformation trends, characteristics, factors and consequences of them which happened in this part of the tribal community. 2- Materials and Methods The present study is a qualitative one in which the sample was selected applying criterion sampling; then using participatory techniques, the changes of the community were investigated. The data were collected from snowball sampling technique and interview with 12 people reached theoretical saturation to understand the changing of effective mechanism in residential- Livelihood patterns. Besides, Grounded Theory was used to analyze the qualitative data. In Grounded Theory analysis, the trend of data obtained from the study is done in three steps namely open coding, axial coding, and selective coding. 3- Results and Discussion Surveying causal conditions related to residential- Livelihood nomad’s manner changing shows a set of forces that can be divided into three categories: Change Internal Forces including the weakness of tribal knowledge and new technologies in relation to livestock, population growth, migration to city, labor shortage, and lack of capital. External forces of change, including land reform, limited support from the government in terms of legal, regulatory and financial entrance of services and facilities to the village, technology penetration among tribes, vulnerability of tribes against natural hazards and human risk, loss of traditional management nomadic, and changing the political structure. Synthesis forces of change includes the loosening of nomadic life values, promoting the culture of consumerism and urban lifestyle. The set of these factors led each family pursues different forms of residential- Livelihood according to their own situation. The following a summary of patterns and different strategies will be introduced. Sedentarization: due to improvement of service and facilities many groups began sedentarization. In this pattern, four livelihood strategies are followed: A) Sedentarized in winter quarters and employment in agriculture and service activities. B) Sedentarized in winter quarters and combines agriculture and livestock (agro pastoralism) C) Migration to the city D) Sedentarized in village and work in the city or elsewhere Semi- nomadism Migration without Livestock or Multi- locational Households The main characteristic of this pattern is the mobility without livestock, moving households done by car and the main willingness to address the activity of farming and gardening. According to respondents, the most important factors in choosing this type of Livelihood approach can be classified as follow: - Suitable natural potential in summer quarter - Natural potential limitations in winter quarter - Influence of technology - Consolidation of ownership - Profitability of gardening comparing to livestock in the current situation 4- Conclusion Nomadism is a residential-Livelihood strategy and art of living in the changing environment. Nowadays, nomadic community have adopted against the set of change forces by different residential- Livelihood strategies. Besides, a set of these forces have changed the landscape in nomadic ecosystems creating different landscapes that nomads have greater adaptation with them. In this change, a lot of structures and functions of nomadism have changed. In the past, livestock was impartible components of nomadic life having the value and dignity among nomads and well- known people who had more livestock in the tribe. In contrast, now, as a complementary activity, it has become even less valuable than agriculture. Nowadays, farming and gardening play an important role in the economy of tribal households. This change in the economic structure of tribal society has led to some changes in the other components of the system having a different role from the past. The changes and transformations have placed different challenges in different aspects of their lives.